KOMUNIKASI PEMASARAN LAYANAN VIDEO STREAMING DAN ON DEMAND MNC GROUP (STUDI KASUS: APLIKASI RCTI+) - Putra, Rizky Ramadhan; Hidayat, Zinggara (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Current TV and video viewing patterns have changed. Viewers were not completely fixated by broadcast hours and broadcast times. In the internet era, people can watch TV anytime and anywhere. Besides, we do not necessarily watch TV shows from the TV set but our smartphone or laptop gadget. Video streaming services are now increasingly popular in various circles because it can be accessed quickly, anytime, and anywhere. As a significant media business in Indonesia, MNC Group is widening its market presence by launching RCTI+ to gain a large share in digital advertising. To complement its already strong FTA position, RCTI+, a multi-application, including the streaming TV and Video on Demand service, is expected to be Indonesia's most extensive streaming service. How marketing communication in the digitization process since MNC Media must reach a new audience is the digital audience. This article will examine how MNC Media conducts communication marketing in the digitization process in its television business by building RCTI+ to reach its new audiences or digital audiences. This paper used the Descriptive Qualitative method, and this research collects data by interviewing the Chief Operating Officer and Dept. Head of Promotion RCTI+, conducting literature and document studies. Based on the research results, RCTI+ integrates its promotional pillars acquisition and retention, running simultaneously to harmonize its marketing communication. RCTI+ strives to build a brand and profitable relationships with customers through these two pillars to create brand equity.